A new species and molecular phylogeny of the Platycerus bashanicus species group (Coleoptera: Lucanidae) endemic to China - Zhang, Sheng-Nan; Xia, Zhong-Yi; Zhao, Ji-Cheng; Su, Chun-Hua; Kubota, Kôhei (Zootaxa, 2026)
A new species in the Platycerus bashanicus species group, Platycerus dabiemontanus Zhang & Kubota, sp. nov., is described from Anhui Province, China. The molecular phylogeny based on mitochondrial COI and nuclear ITS2 sequences indicates a close relationship of this new species with P. yeren Imura, 2008 and P. canae Imura, 2010. Significant mito-nuclear discordance observed between populations suggests the occurrence of mitochondrial gene introgression. This study extends the eastern distribution limit of the P. bashanicus group by 500 km and represents the first record of the genus Platycerus Geoffroy, 1762 from Anhui Province.